Analysis of Information Entropies for He-Like Ions - Hamid Al-Jibbouri (Ital Publication, 2022)
The electronic structure, a special quality of an atomic or molecular system, is the major factor for further realization of physical results. However, in this paper, we present the topical issue of normalized electron density in position and momentum spaces, Shannon, Rényi, and Tsallis entropies to quantify the reach of electron delocalization for several atomic systems. Hartree-Fock-Roothaan (HFR) wave function is performed and considered for He-like ions using single-Zeta ????-type orbital (βTOs) basis set to investigate the affecting of electron density and information entropies. The electron density maxima in position space are raised, and their positions move toward the nucleus as Z increases, in accordance with the increasing attractive force of the nucleus, and vice versa in momentum space. Shannon’s entropy has impacted the delocalization of the electron in different atomic systems. In the limit γ→1, both Rényi and Tsallis entropy results recover Shannon’s entropy value. Rényi and Tsallis entropies decrease by increasing γ. Indeed, the estimated results have been calculated via the Wolfram Mathematica program and have good agreement with the literature results. The obtained results may be a useful reference for future studies on theoretical information quantities. Doi: 10.28991/ESJ-2022-06-04-08 Full Text: PDF